Kekerasan Seksual di Penjara Syariat Melalui @JurnalisKomik - Deviana Fauziyyah Nabilah; Askurifa’I Baksin (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. Today there are various new genres in the world of journalism, one of which is comic journalists who marry journalistic writing with comic illustrations. Like the report titled